Maternal Mortality in Nigeria and Implications for Economic Development (American Journal of Economics and Business Innovation, 2025)
The study examined maternal mortality in Nigeria and its implications for economic development, and it considered the impacts of the maternal mortality ratio on economic growth. The study uses annual time series data spanning 33 observations from 1989 to 2022. Thus, the data’s primary sources are the World Health Organization and the World Bank Development Indicators, 2022. Gross Domestic Product (GDP) serves as the proxy for economic growth, which is the dependent variable, while Fertility Rate (FERATE), Health Expenditure (HEAEXP), and Maternal Mortality Rate (MMR) serve as the exogenous variables. Augmented Dickey-Fuller (ADF) test was utilised to determine the stationarity level of the variables. The Bound and Co-integration Tests show that there exists a long-run relationship among the variables and Fully- modified OLS (FOLS) was used to analyse the Maternal Mortality in Nigeria and Implications for Economic Development from 1989 to 2022 using the E-Views 10 statistical software. In contrast to MMR and FERATE, which have negative relationships with the dependent variable (Gross Domestic Product), HEAEXP has a positive relationship with the dependent variable. The following recommendations were made: Nigeria should increase access to family planning, enhance maternal health services, and provide incentives for smaller families to spur economic growth. Public-private partnerships and open budgeting combined with efficient health spending can improve productivity and healthcare. Lastly, cross-sector cooperation integrating health and economic policies would promote sustainable growth and higher living standards nationwide.